Kajian Kepuasan Pengguna Rumah Bantuan Cinta Kasih Panteriek Banda Aceh - Rika Indriati; Mochammad Afifuddin; Abdul Munir (Prodi Magister Teknik Sipil Unsyiah, 2018)
Post-disaster earthquake and tsunami December 26, 2004 Aceh region suffered a devastation in the field of infrastructure is quite wide, especially housing that amounted to ± 123,000 units. The construction of relief housing for disaster victims by relocating one of them is located in the village of Panteriek Lueng Bata district of Banda Aceh under the name of Cinta Kasih Housing built by Tzu Chi volunteers (Yayasan Budha Tzu Chi Indonesia) of 716 houses. This study aims to determine the level of satisfaction of the people who use Rumah Cinta Kasih Panteriek assistance and analyze the dominant factors of satisfaction level from the location, building design, product quality, facilities and infrastructure. Determination of this research sample using slovin formula obtained 83 house units as a sample of 486 housing units that have not changed shape. Methods used mix methods between qualitative and quantitative where in the primary data collection using cluster sampling technique, then the data is analyzed by index frequency. This research begins with a pre-survey process where tested the questionnaire to determine the level of validity and reliability on each item question tested to 10 respondents. Pre-survey results show that the validity value of 0,31 – 0,70greater than 0.3 while the reliability value 0,86 greater than 0,6 with the sense that the questionnaire is feasible used in this study. The results showed that as many as 16% of respondents answered very satisfied and 28% answered satisfied; 21% answered quite satisfied; 15% answered not satisfied; and 20% of respondents answered very dissatisfied with the Cinta Kasih Panteriek. The dominant factor causing dissatisfaction of the householder is clean water (PDAM or drilled well) with value FI = 0,28; (FI = 0,36), land area (FI = 0,38), and house size (FI = 0,38). While the most dominant factor of the satisfaction of home users is access to the highway with the value of FI = 0,80. From the results of this study it can be concluded that the main cause of dissatisfaction of people in Cinta Kasih Panteriek caused by inadequate network of water supply as basic human needs in carrying out its activities.